2021
DOI: 10.3389/fnhum.2021.647908
|View full text |Cite
|
Sign up to set email alerts
|

Long Multi-Stage Training for a Motor-Impaired User in a BCI Competition

Abstract: In a Mental Imagery Brain-Computer Interface the user has to perform a specific mental task that generates electroencephalography (EEG) components, which can be translated in commands to control a BCI system. The development of a high-performance MI-BCI requires a long training, lasting several weeks or months, in order to improve the ability of the user to manage his/her mental tasks. This works aims to present the design of a MI-BCI combining mental imaginary and cognitive tasks for a severely motor impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Our results show that decoding accuracy increased during the online sessions following the calibration period. This observation is in line with similar studies that have demonstrated improvements in the Cybathlon pilot's BCI control ability due to long-term practice periods -although this has not always translated into high performance on the day of the event, as was the case with the current study and for both [14] and [15]. Possible reasons for this drop in race-day performance, and suggested strategies to address the issue are discussed.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results show that decoding accuracy increased during the online sessions following the calibration period. This observation is in line with similar studies that have demonstrated improvements in the Cybathlon pilot's BCI control ability due to long-term practice periods -although this has not always translated into high performance on the day of the event, as was the case with the current study and for both [14] and [15]. Possible reasons for this drop in race-day performance, and suggested strategies to address the issue are discussed.…”
Section: Discussionsupporting
confidence: 90%
“…Performance accuracy improved by 30% over a three-month training period (20 sessions) -although the user's competition day performance did not re ect this improvement. A similar drop in performance during the Cybathlon competition game, compared to performance during training, has been reported by Turi et al in [15]. They suggested that the drop was due to the indirect impact of stress on performance -expressly the user's psychological state in uenced their ability to concentrate, which affected their performance negatively.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations